Why did I bring you over?!: Looking for a more sheltering regulation of diffuse interests - Campos Ramírez, Raúl (2014)
On this paper, the authors reflect over the article 82 of the Peruvian Procedural Law. that way, they debate over the defense of diffuse interests, specifically who are entitled to and how to reclaim them. then, they compare Peruvian law with other south American countries like uruguay and Brasil. Finally, they consider which would be the most adequate regulation for our society.